Analysis of the Centralized Drug Procurement Results at Ho Chi Minh City Department of Health - Danh, Le Ngoc; Dung, Do Van; Trung, Ly Thanh; Oanh, Chau Thuc; Dat, Truong Van; Thi Hai Yen, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4292, 2021)
This paper analyzes the procurement of drugs by Ho Chi Minh City Department of Health (DoH) through centralized bidding. In the period of 2014-2019, DoH focused mainly on purchasing drugs under generic packages with the quantity ranging from 67% to 70% higher than that of drugs in the original brand name package (30%-33%). In terms of value, compared to the total planned value, the generic package decreased by 65% (2017-2019), while the original brand name package decreased only by 35%. Bid prices and bid winning prices of each commodity decrease over the years. The difference between bid prices and bid winning prices ranged from 20% to 40%. DoH's locally concentrated list of tenders has not yet fully met the needs of the local health facilities, so there is still planning to add new drugs beyond the list. Therefore, it is advisable to conduct a further survey on drug use needs in each health facility through data from open bidding at hospitals in Ho Chi Minh City and from there, to consider which drugs should be added to DoH's centralized drug procurement list. Keywords Centralized bidding, generic bidding package, original brand name bidding package, drug price, HCMC Department of Health References [1] World Health Organization, How pharmaceutical systems are organized in Asia and the Pacific, OECD Publishing, 2018. [2] Government of Vietnam, The World Bank, Fiscal Policies towards Sustainability, Efficiency, and Equity, World Bank Washington DC, 2017. [3] Ministry of health, Circular 09/2016/TT-BYT promulgation of list of drugs for procurement through bidding, list of drugs for concentrated procurement, list of drugs for procurement through price negotiation, 2016 (Vietnamese). [4] Ministry of health, Circular 21/2013/TT-BYT prescribing organization and operation of the drug and treatment council in hospitals, 2013. (Vietnamese). [5] Xuan-Phuoc Nguyen-Thi et al, Analysis of drug bidding results in the form of centralized drug bidding at the Nghe An Province Health Department, Pharmaceutical journal 59 (7), 2019, 03-07 (Vietnamese). [6] Ministry of health, Circular 11/2016/TT-BYT bidding for supply of drugs for public health facilities, 2016 (Vietnamese). [7] Ministry of health, Joint Circular 01/2012/TTLT-BYT-BTC guiding bidding of drugs procurement in the medical facilities, 2012 (Vietnamese).